The Magnetism of Power in Helping Relationships. Professional Attitude and Asymmetry - Theo Schuyt (Social Work & Society, 2004)
What makes helping relationships - or social interventions in general - so sensitive to abuse? These problems are directly related to the nature of the helping relationship. The core of this relationship is the inequality, the asymmetry, between the helper and the person being helped, and the dependence of the latter. Asymmetry is the driving force behind every social intervention and at the same time its weakest point. Handling asymmetry in an appropriate manner constitutes a major part of the work of the intervening party. This asymmetry makes heavy demands on the professional attitude of the intervening party i.e. the helper. Is s/he capable of dealing with dependence in an acceptable way? Is s/he well-versed in her/his profession? This article contains a comprehensive sketch of many of the possible dangers and pitfalls which beset asymmetric intervention relations. At the end it will be argued that, for a better understanding, the proximity of helping and power has to be taken into account.